Experiencing fear appeals as a challenge or a threat influences attainment value and academic self-efficacy. (December 2015) - Putwain, David W.; Remedios, Richard; Symes, Wendy
Abstract: Fear appeals are persuasive messages that highlight the negative consequences of a particular course of action. Studies have shown that attainment value and academic self-efficacy predict how fear appeals are appraised. In this study we examined how the appraisal of fear appeals might also influence subsequent attainment value and academic self-efficacy. Self-report data were collected from 1433 students in their final two years of secondary education over three waves. Findings revealed that when students saw fear appeals as a challenge attainment value and academic self-efficacy were higher. When students saw fear appeals as a threat, attainment value and academic self-efficacy were lower. These results highlight the functional importance of how fear appeals are appraised. Challenge and threat appraisals were not mere by products of attainment value or academic self-efficacy but impacted on attainment value and academic self-efficacy; variables that are likely to make a critical impact on educational progress and attainment. We conclude that initial teacher education and teacher professional development programs would benefit from enhanced interpersonal and relational-skills training to enable teachers to judge more effectively how fear appeals are appraised. Highlights: Fear appeals can be appraised as challenging or threatening. A threat appraisal resulted in lower attainment value and academic self-efficacy. A challenge appraisal resulted in higher attainment value and academic self-efficacy.